2003
DOI: 10.1165/rcmb.2002-0180oc
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of Claudin Expression by Alveolar Epithelial Cells

Abstract: Claudins are proteins that participate in epithelial barrier function and regulate paracellular permeability. By immunohistochemistry of adult rat lung sections, claudin-3, claudin-4, and claudin-5 were found to be co-expressed by type II alveolar epithelial cells. Claudin-3 and claudin-4 were also co-expressed by some alveolar epithelial cells adjacent to type II cells. In contrast, claudin-5 was expressed throughout the alveolus. Isolated primary rat alveolar epithelial cells in culture also expressed claudi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
125
1
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 138 publications
(140 citation statements)
references
References 52 publications
13
125
1
1
Order By: Relevance
“…Our original identification of MBEC1/claudin-5 mRNA and protein expression by the endothelial cells of the BBB (8) has subsequently been confirmed by others (34,41,42). In addition to BBB and other endothelial cells, our studies (8) and those of others (32,35,45,56) have revealed claudin-5 expression in epithelial cells as well as other specialized cell types, including pancreatic acinar cells (45) and myelinating Schwann cells in nerves (44).…”
Section: Discussionsupporting
confidence: 70%
“…Our original identification of MBEC1/claudin-5 mRNA and protein expression by the endothelial cells of the BBB (8) has subsequently been confirmed by others (34,41,42). In addition to BBB and other endothelial cells, our studies (8) and those of others (32,35,45,56) have revealed claudin-5 expression in epithelial cells as well as other specialized cell types, including pancreatic acinar cells (45) and myelinating Schwann cells in nerves (44).…”
Section: Discussionsupporting
confidence: 70%
“…Reduced expression of claudin-5 as seen in the present study has been associated with increased permeability in several previous studies (Kirk et al, 2003;Kitajima et al, 2006;Kniesel and Wolburg, 2000;Tsukita and Furuse, 1998). While transfection of claudin-5 into epithelial cells with a low electrical resistance enhances barrier function (Amasheh et al, 2005), overexpression of claudin-5 results in a loss of barrier function and increased permeability and paracellular volume of distribution (Coyne et al, 2003;Kojima et al, 2002;Wang et al, 2003). Knocking out the claudin-5 gene is lethal within 10 h of birth, and BBB TJs become more permeable to molecules <800 Da, but not larger (Nitta et al, 2003).…”
Section: Discussionsupporting
confidence: 66%
“…For instance, if heterotypic incompatibility (e.g. between claudin-5 and claudin-4) is a dominant interaction in lung epithelia, then increased claudin-5 expression would be expected to compromise tight junction integrity, as previously observed (31). Conversely, in the endothelium, claudin-5 may be compatible with the other major endothelial claudin, claudin-12 (34).…”
Section: Discussionmentioning
confidence: 78%